Desain Pemanfaatan Bahan Peledak Expired Dan Failur Menggunakan Metode Sloping Dan Molding Berperspektif FAST Dan HIRADC (Usability Design for Expired and Failure Explosive through Sloping and Molding Methods with FAST dan HIRADC Perspective - Sulistyawati, Nunik Endah (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2022)
Explosives come from natural resources, which were initially just ordinary materials or compounds where humans did not yet know the elements, functions, and effects. With time, humans conducted research when they saw the reactions arising from natural chemical reduction's effects. This research developed as a refinement of explosive products from time to time according to the functions and benefits for the benefit of the development of a region or country. International crime has become a threat to countries around the world. The development of technology and the flow of information resulted in a new order of life in various dimensions. The circulation of weapons or conventional explosives that weapons manufacturers have made is in great demand by many countries, including the Indonesian nation, as a tool used and used by the TNI to maintain security and maintain the sovereignty of the Unitary State of the Republic of Indonesia. Adopting these problems, further research can be carried out on expired/failed explosives to be reused for their functions. The extermination that has been carried out so far poses a risk to the environment and living things. The use of explosives using the sloping and molding method designed with FAST and HIRADC in mind is expected to provide a solution to minimize risks to both the environment and living creatures around it.